Intralymphatic immunotherapy for cat allergy induces tolerance after only 3 injections - Senti, Gabriela; Crameri, Reto; Kuster, Daniela; Johansen, Pål; Martinez-Gomez, Julia M.; Graf, Nicole; Steiner, Martin; Hothorn, Ludwig A.; Grönlund, Hans; Tivig, Christine; Zaleska, Anna; Soyer, Ozge; et al. (Journal of allergy and clinical immunology, 2012)
Subcutaneous allergen-specific immunotherapy frequently causes allergic side effects and requires 30 to 80 injections over 3 to 5 years. We sought to improve immunotherapy by using intralymphatic allergen administration (intralymphatic immunotherapy [ILIT]) and by targeting allergen to the MHC class II pathway. Recombinant major cat dander allergen Fel d 1 was fused to a translocation sequence (TAT) and to part of the human invariant chain, generating a modular antigen transporter (MAT) vaccine (MAT–Fel d 1). In a randomized double-blind trial ILIT with MAT–Fel d 1 in alum was compared with ILIT with placebo (saline in alum) in allergic patients (ClinicalTrials.govNCT00718679). ILIT with MAT–Fel d 1 elicited no adverse events. After 3 placebo injections within 2 months, nasal tolerance increased less than 3-fold, whereas 3 intralymphatic injections with MAT–Fel d 1 increased nasal tolerance 74-fold (P < .001 vs placebo). ILIT with MAT–Fel d 1 stimulated regulatory T-cell responses (P = .026 vs placebo) and increased cat dander–specific IgG4 levels by 5.66-fold (P = .003). The IgG4 response positively correlated with IL-10 production (P < .001). In a first-in-human clinical study ILIT with MAT–Fel d 1 was safe and induced allergen tolerance after 3 injections.